Foreword - Szövényi, Anna (4D Tájépítészeti és Kertművészeti Folyóirat, 2025)
It is now hard to deny that our climate is changing rapidly. In summer in Hungary, life in urban areas is slowly becoming intolerable. What is the solution? Can we, as humans, react quickly and in time to the negative environmental challenges that we ourselves have created? When choosing a topic for their degree, students try to address the issues that are most relevant to them and of most interest to the wider public. What are the green solutions of future? What is the future of our cities, our landscapes, our urban landscapes? A majority of the student projects presented in the diploma issue focus on climate adaptation, increasing the intensity of green spaces and enhancing biodiversity, while others are working on solutions to social issues or technical innovation. The range of plans and dreams is diverse. Yet what are the key elements in which our students believe the solution lies?